AUGMENTED REALITY ON ANDROID OPERATING SYSTEM- BASED DEVICE;CASE STUDY: MOSQUE FINDER - Ary Mazharuddin S; Diaz Hendrianto (Jurnal Ilmiah Kursor, 2012)
Augmented Reality (AR) has become one of research trends in the utilization of virtual object modeling. AR works by modeling objects that exist in the real world into a vitual world by using input devices. The input devices can be a camera, sensor, or even GPS. AR can work in real time fashion to show the movement of a real object by using a form of model shown at monitor screen.This research developed an Augmented Reality for locating a mosque. Augmented Reality (AR) is a technology that combines two-dimensional virtual object into a three-dimensional environment then displays the virtual objects in real-time fashion. To implement the AR concept, this application uses integrated sensors such as accelerometer, compass and Global Positioning System (GPS). The location of mosques are downloaded from a dedicated server and stored in asmartphone. In order to anticipate should there is an update of data at the database; this application is also equipped with synchronization feature using a web service with XML technology. Experiment results show that the mosques location searching can be performed smoothly with the augmented reality technique. The details of the location of the mosque can be accurately displayed at the handled device. Augmented Reality (AR) has become one of research trends in the utilization of virtual object modeling. AR works by modeling objects that exist in the real world into a vitual world by using input devices. The input devices can be a camera, sensor, or even GPS. AR can work in real time fashion to show the movement of a real object by using a form of model shown at monitor screen.This research developed an Augmented Reality for locating a mosque. Augmented Reality (AR) is a technology that combines two-dimensional virtual object into a three-dimensional environment then displays the virtual objects in real-time fashion. To implement the AR concept, this application uses integrated sensors such as accelerometer, compass and Global Positioning System (GPS). The location of mosques are downloaded from a dedicated server and stored in asmartphone. In order to anticipate should there is an update of data at the database; this application is also equipped with synchronization feature using a web service with XML technology. Experiment results show that the mosques location searching can be performed smoothly with the augmented reality technique. The details of the location of the mosque can be accurately displayed at the handled device.